Moving sociohydrology forward: a synthesis across studies - T. J. Troy; M. Konar; V. Srinivasan; S. Thompson (Hydrology and Earth System Sciences, 2015)
Sociohydrology is the study of coupled human–water systems, building on the premise that water and human systems co-evolve: the state of the water system feeds back onto the human system, and vice versa, a situation denoted as "two-way coupling". A recent special issue in HESS/ESD, "Predictions under change: water, earth, and biota in the Anthropocene", includes a number of sociohydrologic publications that allow for a survey of the current state of understanding of sociohydrology and the dynamics and feedbacks that couple water and human systems together, of the research methodologies being employed to date, and of the normative and ethical issues raised by the study of sociohydrologic systems. Although sociohydrology is concerned with coupled human–water systems, the feedback may be filtered by a connection through natural or social systems, for example, the health of a fishery or through the global food trade, and therefore it may not always be possible to treat the human–water system in isolation. As part of a larger complex system, sociohydrology can draw on tools developed in the social–ecological and complex systems literature to further our sociohydrologic knowledge, and this is identified as a ripe area of future research.